CpG-Activated Regulatory B-Cell Progenitors Alleviate Murine Graft-Versus-Host-Disease - Agbogan, Viviane A.; Gastineau, Pauline; Tejerina, Emmanuel; Karray, Saoussen; Zavala, Flora (Frontiers in Immunology, 2022)
Development of Graft Versus Host Disease (GVHD) represents a major impediment in allogeneic hematopoietic stem cell transplantation (HSCT). The observation that the presence of bone marrow and circulating hematogones correlated with reduced GVHD risks prompted us to evaluate whether B-cell progenitors, which provide protection in various autoimmune disease models following activation with the TLR-9 agonist CpG (CpG-proBs), could likewise reduce this allogeneic disorder. In a murine model of GVHD that recapitulates an initial phase of acute GVHD followed by a phase of chronic sclerodermatous GVHD, we found that CpG-proBs, adoptively transferred during the initial phase of disease, reduced the diarrhea score and mostly prevented cutaneous fibrosis. Progenitors migrated to the draining lymph nodes and to the skin where they mainly differentiated into follicular B cells. CpG activation and IFN-γ expression were required for the protective effect, which resulted in reduced CD4+ T-cell-derived production of critical cytokines such as TGF-β, IL-13 and IL-21. Adoptive transfer of CpG-proBs increased the T follicular regulatory to T follicular helper (Tfr/Tfh) ratio. Moreover, CpG-proBs privileged the accumulation of IL-10-positive CD8+ T cells, B cells and dendritic cells in the skin. However, CpG-proBs did not improve survival. Altogether, our findings support the notion that adoptively transferred CpG-proBs exert immunomodulating effect that alleviates symptoms of GVHD but require additional anti-inflammatory strategy to improve survival.